EFFECT OF PRECIPITATION HARDENING ON MICROSTRUCTURE OF 17-7 PH STEEL WITH MODIFIED CHEMICAL COMPOSITION - Belma Fakić; Derviš Mujagić; Omer Beganović (Journal of Sustainable Technologies and Materials, 2024)
Steel 17-7PH is austenitic-martensitic steel with high strength, hardness, and resistance to creep, and corrosion. It is designed for aerospace components, but can also be used for other applications that require high strength and corrosion resistance, as well as leaf springs for operation at temperatures up to 316 °C. It can be used in a solution-treated or heat-treated state to obtain a wide range of property values. This paperwork shows that modification of the contents of alloying elements with a narrower interval of Cr, Ni, and Al can be obtained from austenitic-martensitic steel 17-7PH which by, a subsequent heat treatment, can have values of mechanical and chemical properties required for components of an automotive engine. Chromium is an alphagenic alloying element that stabilizes the ferrite region, nickel is a gammagenic alloying element that stabilizes austenite and gives these steels good strength and toughness, even at low temperatures and aluminum increases corrosion resistance in low-carbon corrosion-resistant steels Research has determined the most suitable interval of Cr, Ni, and Al, which in combination with thecryogenic heat treatment RH950 at -50 °C gives the mechanical and chemical properties that meet the requirements for steel with standard chemical composition.